Implementation of the Sustainable Development Goals (SDG's) Application in Putridalem Village, Majalengka Regency" - Dea Nuramalia; Imas Della Menanda (Social Impact Journal, 2022)
The village is one element of the government that has the right and obligation to regulate the wheels of government. Currently, the Village has launched an application called the Village Sustainable Development Goals (SDGs). The application of the Village's Sustainable Development Goals (SDGs) aims to find out the extent of sustainable development in Putridalem Village, the local government needs to align the three core elements in the application of these Sustainable Development Goals (SDGs). The three core elements include Economic growth, social inclusion, and environmental protection. This article aims to see the extent of the implementation of the Sustainable Development Goals (SDGs) application in Putridalem Village, Majalengka Regency. The research method used in this study is a qualitative research method with descriptive analysis through interviews and literature studies. The results of this study found that the implementation of the Sustainable Development Goals (SDGs) application in Putridalem Village can be said to be not optimal because there are still obstacles in running the SDGs application.